Working Capital Level Influence on SME Profitability - Afrifa, G.; Padachi, Kesseven (Emerald Group Publishing Limited, 2015)
This paper aims to report the results of an investigation of the relationship between working capital level, measured by the cash conversion cycle and profitability of Small and Medium Enterprises (SMEs). The paper employs panel data regression analysis on a sample of 160 Alternative Investment Market (AIM) listed SMEs for the period from 2005 to 2010. The empirical results show that there is a concave relationship between working capital level and firm profitability and that there is an optimal working capital level at which firms’ profitability is maximised. Furthermore, an examination as to whether or not deviations from the optimal working capital level reduce firm profitability indicate that deviations above or below the optimum decrease profitability. The sample is limited to AIM listed SMEs, and therefore the findings cannot be generalised to all firms. Overall, the evidence suggests that firms should strive and attain the optimal working capital level in order to maximise their profitability. The results are of importance to both SMEs and policy makers providing insight into the nature of cash conversion cycle and its relationship to SMEs profitability